(0, 2; 0)-INTERPOLATION ON THE UNIT CIRCLE - Bahadur, Swarnima (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we study the explicit representation and convergence of P´al-type weighted (0, 2; 0)-interpolation on two pairwise disjoint sets of nodes on the unit circle, which are obtained by projecting vertically the zeros of (1− x2) Pn(x) and P′n(x) respectively on the unit circle, where Pn(x) stands for nth Legendre polynomial.